2018
DOI: 10.5433/1679-0359.2018v39n4p1389
|View full text |Cite
|
Sign up to set email alerts
|

Productivity in seeds of the green bean produced under conventional and organic systems

Abstract: Two experiments were carried out during 2016 at the Anápolis Experimental Station of EMATER in the State of Goiás, with the aim of studying the yield of seeds of 18 strains and two indeterminate cultivars of the green bean, one experiment under a conventional system and the other under an organic system. A randomized block experimental design was used, with twenty treatments and three replications, to evaluate the mean number of seeds per pod (NSP), 100-seed weight (100SW) and productivity (PROD). Under the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Higher yield values found in the conventional cultivation system are in agreement with Brunner et al (2014), who found, in na organic system in Puerto Rico, Panama, yields of marketable pods superior to those found in conventional system. They also agree with Portal et al (2018), who, studying genotypes of wild bean of indeterminate growth, in the same place, also found better yield performance in organic production system.…”
Section: /6supporting
confidence: 90%
“…Higher yield values found in the conventional cultivation system are in agreement with Brunner et al (2014), who found, in na organic system in Puerto Rico, Panama, yields of marketable pods superior to those found in conventional system. They also agree with Portal et al (2018), who, studying genotypes of wild bean of indeterminate growth, in the same place, also found better yield performance in organic production system.…”
Section: /6supporting
confidence: 90%
“…In this sense, Néri et al (2020) evaluated, in Anápolis, regarding seed production, 20 bush snap bean genotypes in conventional and organic systems, with most genotypes being more productive in the organic system. Portal et al (2018), studying 20 bean genotypes of indeterminate growth, in the same location, of both systems, also obtained better productive performance in the organic system.…”
Section: Introductionmentioning
confidence: 78%
“…Diabrotica speciosa and Bemisia tabaci were controlled by spraying with Neem oil associated with biofertilizer, according to the recommendations of the manufacturer. The variables studied in both experiments were: 1) yield of green pods (at the stage considered suitable for commercialization), obtained by the sum of the mass of three harvests in each plot, expressed in tons per hectare; 2) average mass of pods, obtained by the division of the total mass of pods by the total number of pods in each plot, expressed in grams; 3) number of pods per plant, obtained by the division of the total number of pods by the number of plants in the plot; and 4) plant vigor, evaluated in the flowering phase, using a scale of notes from 1 to 5, where 1 is low vigor, and 5 is high vigor (Portal et al, 2018). Data were subjected to analysis of variance for each experiment, followed by the joint analysis.…”
Section: Methodsmentioning
confidence: 99%